Human brain local field potential recordings during a battery of multilingual cognitive and eye-tracking tasks - J. Cimbalnik; J. S. Garcia-Salinas; N. Hamedi; S. Prathapagiri; L. F. Sarmiento Rivera; M. Galanina; J. Dolezal; L. Jurkovicova; P. Daniel; M. Kojan; R. Roman; M. Pail; et al. (Scientific Data)
Abstract Intracranial human brain recordings from multiple implanted depth electrodes using stereo-EEG (sEEG) technology for seizure localization provide unique local field potential signals (LFP) sampled with standard macro- and special micro-electrode contacts. Over one hundred macro- and micro-contact LFP signals localized in particular brain regions were recorded from each sEEG monitoring case as patients engaged in an automated battery of verbal memory and non-verbal gaze movement tasks. Subject eye and vocal responses in both visual and auditory task versions were automatically detected in Polish, Czech, and Slovak languages with accurate timing of the correct and incorrect verbal responses using our web-based transcription tool. The behavioral events, LFP and pupillometric signals were synchronized and stored in a standard BIDS data structure with corresponding metadata. Each dataset contains recordings from at least one battery task performed over at least one day. The same set of 180 common nouns in the three languages was used across different battery tasks and recording days to enable the analysis of selective responses to specific word stimuli.